O redesenho em BIM: o processo integrado de projeto e a análise da simulação construtiva - Silva, Rangel Henrique Brandão (2019)
Although BIM (Building Information Model) isn't an exclusivity in project integrated practice, it's a potentiator and stands like a new work platform that subscribes for project integrated process, constructive management and a building maintence. The possibility of existing a computer model where all the building informations are available to all the designers is worth it, because it contributes to a most faithful and compatible project and construction. Therefore, it’s important how this work platform helps, influences or contests parts of the architect’s project process. According to this question, this research presents a reflection about the project integrated process in a traditional way or in BIM. It also performs a comparative exercise between the building, from traditional integration and virtual construction simulation, according to BIM model integration. For this research’s development, it was done a referential review about the BIM concepts and the building project integrated process. It was also done an interview with the coordination projects responsible architect, then it was developed a BIM model, based on the original architectural, structural, hydraulic and electrical projects. As a result, it was presented a project integrated process analysis of Espaço architecture office and a virtual construction simulation. The interferences and divergencies found in the model were confronted with the original project solutions, with the coordination responsible architect report, and with in loco building observation, built in the 1970s. Therefore, this research supports the platform use improvement in coordination and project process management, increasing the comprehension of the architect's role, the method and the BIM use on this “new” culture of project integration.